2014
DOI: 10.1186/s13068-014-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Domestication of the green alga Chlorella sorokiniana: reduction of antenna size improves light-use efficiency in a photobioreactor

Abstract: BackgroundThe utilization of biomass from microalgae for biofuel production is one of the key elements for the development of a sustainable and secure energy supply. Among the different microalgae, Chlorella species are of interest because of their high productivity, high lipid content, and resistance to the high light conditions typical of photobioreactors. However, the economic feasibility of growing algae at an industrial scale is yet to be realized, in part because of biological constraints that limit biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 61 publications
5
105
0
4
Order By: Relevance
“…However, this increase in yield needs to be coupled with improvements in phototrophic algal biomass production in order to make the platform commercially competitive. Such improvements will come from a combination of media optimization [66], improvements in photobioreactor (PBR) design [67] and strain domestication, such as selection for reduced light-antenna mutants that show higher productivity in PBRs as a consequence of greater light penetration [68]. Alternatively, it might be more cost-effective to switch to mixotrophic production in PBRs, or heterotrophic cultivation in fermenters, where much higher biomass productivity can be achieved [69].…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…However, this increase in yield needs to be coupled with improvements in phototrophic algal biomass production in order to make the platform commercially competitive. Such improvements will come from a combination of media optimization [66], improvements in photobioreactor (PBR) design [67] and strain domestication, such as selection for reduced light-antenna mutants that show higher productivity in PBRs as a consequence of greater light penetration [68]. Alternatively, it might be more cost-effective to switch to mixotrophic production in PBRs, or heterotrophic cultivation in fermenters, where much higher biomass productivity can be achieved [69].…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…To achieve an intermediate antenna size, the synthesis of Chl b, which is bound only to the peripheral light-harvesting antenna complex proteins, was reduced by inhibiting the synthesis of Chl a oxygenase, the enzyme that converts Chl a into Chl b, using RNAi technology (Perrine et al, 2012). Most recently, this approach to reduce antenna size, and thus increase biomass productivity, was performed in C. sorokiniana, where UV mutagenesis was utilized to isolate truncated antenna mutants (Cazzaniga et al, 2014). PSII antenna reduction (48% of LHCII protein content compared to www.frontiersin.org wild-type) resulted in a 32% increased mean biomass productivity over wild-type strains when grown in photobioreactors.…”
Section: Increasing Solar Energy Capture and Conversion Efficiency Fomentioning
confidence: 99%
“…In many cases wrong definitions are used for 'productivity' (Cazzaniga et al 2014) and 'growth rate' (Perrine et al 2012). This has led to the often quoted claim that antenna size mutant technology could triple the biomass productivity compared to wild type cells (Melis 2009), which is not-substantiated.…”
Section: Quantifying Biomass Productivity Under Mass Culture Conditionsmentioning
confidence: 99%
“…Microalgae have been reported to radically increase their NPQ capacity even at moderate light intensities (Bonente et al 2012, Cazzaniga et al 2014 2014), though in one study, it was shown that the total contribution of these screening pigments to total NPQ was limited (Masojídek et al 1999). We did not measure a relative change in the absorption spectrum after a transfer from high light to mass culture.…”
Section: Possible Explanations For the Discrepancy Between The Model mentioning
confidence: 99%
See 1 more Smart Citation